Methods for Assessing Mucociliary Transport and Nasal Patency: A Physiological Review - Daniel Pradana Andrian Wicaksono; Arin Dwi Iswarini (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2026)
Methods for Assessing Mucociliary Transport and Nasal Patency: A Physiological Review Background: Mucociliary transport and nasal patency are essential physiological components in maintaining respiratory function and upper airway defense mechanisms. Impairment of these systems may reduce mucosal clearance efficiency, increase airflow resistance, and contribute to inflammatory and infectious conditions of the nasal cavity and paranasal sinuses. Accurate evaluation of mucociliary function and nasal patency is therefore important in both clinical practice and rhinology research. Objective: This literature review aims to discuss various methods for assessing mucociliary transport and nasal patency based on their underlying physiological principles. Literature Review: Mucociliary transport can be assessed using subjective methods such as the saccharin test and objective methods including digital high-speed videomicroscopy and scintigraphy radioisotope clearance test. Nasal patency may be evaluated using subjective approaches such as the Visual Analog Scale (VAS) and Nasal Obstruction Symptom Evaluation (NOSE), as well as objective techniques including Peak Nasal Inspiratory Flow (PNIF), rhinomanometry, and acoustic rhinometry. Each method has distinct principles, advantages, and limitations in representing structural and functional aspects of nasal physiology. Conclusion: Understanding the physiological basis and characteristics of each assessment method is essential to improve clinical interpretation and to guide the appropriate selection of evaluation techniques in rhinology practice and research.